INITIAL ANALYSIS OF STUDENTS SCIENCE LITERACY ON ALTERNATIVE ENERGY MATERIAL - rahmadani, anisya (Department of Physics Universitas Negeri Padang, 2024)
Scientific literacy is one of the skills that symbolizes expanding knowledge and resolving issues. PISA 2018 findings, however, show that scientific literacy in Indonesia is still very poor. Aspects of students' scientific literacy, including their capacity to evaluate and plan scientific research, interpret data and scientific evidence, and explain occurrences scientifically, will be examined in this study. Analyzing students' scientific literacy in alternative energy content was the aim of this study.. The method used is quantitative descriptive using a scientific literacy test instrument in the form of questions for students and questionnaires for teachers on alternative energy material used to collect data. Twenty-five students and two physics professors made up the research sample. The findings of the examination of two instructors' learning implementation were 60.48%. The average overall competency domain indicator was 47.80% with a very low category, based on students' mastery of scientific literacy in the competency domain indicator explaining scientific phenomena (51.42% with a low category), evaluating and designing scientific investigations (68% with a moderate category), and interpreting data and scientific evidence (24% with a very low category). Thus, it can be said that pupils' scientific literacy regarding alternative energy content is still rather low.